Amodal Atypical Neural Oscillatory Activity in Dyslexia: A Cross-Linguistic Perspective. (March 2017) - Lallier, Marie; Molinaro, Nicola; Lizarazu, Mikel; Bourguignon, Mathieu; Carreiras, Manuel
It has been proposed that atypical neural oscillations in both the auditory and the visual modalities could explain why some individuals fail to learn to read and suffer from developmental dyslexia. However, the role of specific oscillatory mechanisms in reading acquisition is still under debate. In this article, we take a cross-linguistic approach and argue that both the phonological and orthographic specifics of a language (e.g., linguistic rhythm, orthographic depth) shape the oscillatory activity thought to contribute to reading development. The proposed theoretical framework should allow future research to test cross-linguistic hypotheses that will shed light on the heterogeneity of auditory and visual disorders and their underlying brain dysfunction(s) in developmental dyslexia, and inform clinical practice by helping us to diagnose dyslexia across languages.